Japan, the US, and Official Development Assistance to the Philippines - Tadem, Eduardo C. (Kasarinlan: Philippine Journal of Third World Studies, 2008)
The Philippine Assistance Plan (PAP), alternately called Multilateral Aid Initiative (MAI) and Mini-Marshall Plan, was initiated by the United States in 1988 as a program to infuse massive amounts of new and additional foreign aid into the Philippines to start off the Marcos-ravaged economy on the road to economic recovery. This article discusses PAP as old money, the evils of ODA, Japan's central role, the conditionalities attached to the PAP, the backlog in the aid pipeline, etc.